Study on optimization of extraction and purification processes for total flavonoids from Lycopi herba roots and their anti-proliferative effects on fibrous synoviocytes in human rheumatoid arthritis - Jie Chen; Chunyang Jiang; Zhenyu Liu; Panpan Wang; Qiang Ma; Nong Zhou (Ultrasonics Sonochemistry)
Lycopi herba, a traditional Chinese medicinal plant, has long been valued for its aerial parts. however, its roots, which are often discarded as non-medicinal waste, actually contain flavonoid compounds that possess potential medicinal values such as anti-inflammatory, antioxidant, and anti-tumor activities. Despite this, studies on the extraction, purification, and biological activity assessment of total flavonoids from L. herba roots (TFLHR) remain inadequate. Our study aimed to optimize the extraction and purification processes for TFLHR and evaluate their anti-proliferative effects on human fibroblast-like synoviocytes (HFLS-RA), which are key pathological cells in rheumatoid arthritis. By utilizing ultrasound-assisted extraction combined with response surface methodology (RSM), we optimized the extraction conditions, achieving a total flavonoid content of 90.484 ± 0.974 mg/g under the optimal settings: a liquid–solid ratio of 48:1 mL/g, 13 min of ultrasound treatment, 70 % ethanol, and an extraction temperature of 43°C. Subsequently, macroporous resin chromatography was employed for flavonoid purification, with AB-8 resin exhibiting the highest performance, achieving adsorption and desorption rates of 79.64 ± 1.51 % and 88.61 ± 1.02 %, respectively. By further refining the purification conditions through RSM, the purity of flavonoids was increased to 63.9 ± 1.86 %. Through ultra performance liquid chromatography tandem-quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS/MS) analysis, 74 flavonoid compounds across 15 categories were identified. Further activity studies demonstrated that purified TFLHR exhibited significant concentration-dependent anti-proliferative effects on HFLS-RA cells. This study not only provides a scientific basis for the comprehensive utilization of L. herba root resources but also highlights the potential medicinal value of TFLHR in the treatment of rheumatoid arthritis, laying a foundation for future research into its specific mechanisms and clinical applications.